Process optimisation for oil and gas platform with process integration techniques - Pitchaimuthu, Diban (2019)
Heating utility system is commonly used in offshore platform to provide heating requirement for heavy crude oil of high viscosity from the reservoir. Heating the oil reduces its viscosity and improves oil/water separation which eventually leads to reduced size and cost of the separator. In conventional design, heating medium is distributed to the heat exchangers in parallel configuration to provide the required heating. All heat exchangers will receive the heating medium at supply temperature in this configuration. This parallel design however contributes to the overdesign of heating utility system. Besides, the phase separation system which separates the heated crude oil into oil, water and gas is designed independently. No prior study has been reported to investigate the interactions of the two systems. The independent design approach may lead to increase overall cost of both systems. Hence, it is the subject of this thesis to address the above research gap.